2022
DOI: 10.1002/cjce.24623
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous enzymatic extraction and quality evaluation of Acer truncatum Bunge seed oil

Abstract: Aqueous enzymatic extraction (AEE) of oil from Acer truncatum Bunge seed kernel was investigated. The effects of enzyme type on the extraction yield of oil were studied, and the results showed that the oil yield obtained with pentosanase was higher than that obtained with the other enzymes. The combination of pentosanase and cellulase showed better extraction performance than a single enzyme, and the operation parameters of the AEE method were optimized. A maximum oil yield of 37.94% was obtained. The analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…From the processing technology perspective, a decrease in yield was observed in the following order: AEE (56.4–59.7%) > HE (56.5–59.5%) > SBE (45.8–47.6%) > CP (35.4–39.9%). The high AEE yield revealed that the enzyme degraded the HOR cell wall more effectively, leading to a higher release of oil and other materials trapped within the cells, into the aqueous medium, resulting in an improved yield ( Hu et al, 2022 ). The lowest oil yield was obtained from roasting-pretreated-CP (R-CP) oil, because roasting may decrease the water content of HOR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the processing technology perspective, a decrease in yield was observed in the following order: AEE (56.4–59.7%) > HE (56.5–59.5%) > SBE (45.8–47.6%) > CP (35.4–39.9%). The high AEE yield revealed that the enzyme degraded the HOR cell wall more effectively, leading to a higher release of oil and other materials trapped within the cells, into the aqueous medium, resulting in an improved yield ( Hu et al, 2022 ). The lowest oil yield was obtained from roasting-pretreated-CP (R-CP) oil, because roasting may decrease the water content of HOR.…”
Section: Resultsmentioning
confidence: 99%
“…AEE has significant advantages in energy consumption and environmental sanitation. It uses an enzyme to destroy the vegetable cell wall via mechanical disruption, to release the oil ( Hu et al, 2022 ). Alcalase can release oil droplets more efficiently by destroying the cell wall and hydrolyzing lipoproteins to obtain a high oil yield.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al obtained the seed essential oil of Acer truncatum Bunge s through liquid oil pressing and CO 2 supercritical extraction technology, and purified NA by high-speed countercurrent chromatography with a content of 18.1% 20) . Xu et al used aqueous enzymatic extraction to extract the seed oil of Acer truncatum Bunge and obtained fatty acid with good quality, with a NA content of 7.2% 21) . However, problems such as seed breakage during collection and seed oil loss during extraction remain to be solved.…”
Section: Isolation Of Namentioning
confidence: 99%